Discovering the dementia evidence base: Tools to support knowledge to action in dementia care (innovative practice). (September 2016) - Hayman, Sarah L; Tieman, Jennifer J
Dementia requires expert care and decision making, based on sound evidence. Reliable evidence is difficult for busy dementia care professionals to find quickly. This study developed an experimentally tested search filter as an innovative tool to retrieve literature on dementia. It has a known retrieval performance and can be provided as an open access web link directly to current literature. The Dementia Search Filter was developed using validated methodology. An Expert Advisory Group of dementia care practitioners and researchers ratified a representative set of relevant studies and undertook post hoc relevance assessment, to ensure the usefulness of the search filter. The Dementia Search Filter is published on two websites and combined with expert searches to link to evidence on dementia, at end of life in aged care settings and more generally. Evidence accessed by the Dementia Search Filter will help overcome barriers to finding current relevant research in the field, for practitioners, researchers and decision makers.